EFFECTS OF LEARNING GUIDED DISCOVERY USING MAP CONCEPT OF PROCESS SKILLS AND ABILITIES COGNITIVE SCIENCE PHYSICS STUDENTS SMA - Meri Pinta Ulin; Karya Sinulingga (Universitas Negeri Medan, 2015)
The purpose of this study were to analyze science process skill and physics cognitive competence taught of students by guided discovery learning by using the concept maps or taught by conventional learning. The research type was quasi experiment with the two group pre-test and post test design, and the population of this study was all students class X semester II at senior high school 1 Pancur Batu. The research sample was taken by simple random sampling technique consist of two class, theyare the experimental class taught by the guided discovery learning by using the concept maps and the control class taught by the conventional learning. The data of this research was taken using observation sheet to see the science process skill of students and multiple choice test to see the students’ physics cognitive competence. The result showed that the average value of science process skills of students in the experimental class is 69.26, while in the control class 47.72 and cognitive competence taught of students' physics class experiment was 81.33, while in the control class 75.50. The results of this research indicated that science process skill of students on and physics cognitive competence taught by the guided discovery learning by using the concept maps was better than taught by the conventional learning.